Soil fauna associated with different cultivation systems (Research, Society and Development, 2021)
The edaphic fauna has been widely used as a bioindicator of soil quality in agroecosystems because it responds quickly to changes resulting from the use and management of agricultural systems. The objective of this study was to evaluate soil fauna associated with conventional and sustainable cultivation systems. The studied systems were conventional cane, organic cane, organic corn intercropped with pigeon pea dwarf, organic corn in monoculture, agroforestry system, fallow soil, and native vegetation. Four pitfall traps were installed in each area to capture soil fauna organisms, along a transect, equidistant to 5 m, totaling 28 traps. A total of 1330 individuals were collected, distributed in 50 taxa, with Formicidae, Collembola, and Diptera: Phoridae the predominant ones. Individuals belonging to the predatory functional trophic group were the most representative in most of the areas studied. The fallow, agroforestry, conventional cane, and native vegetation systems showed a greater abundance of soil fauna individuals. The richness of groups was higher in systems with organic maize in monoculture, intercropped with pigeon pea and fallow, with the two maize areas showing greater uniformity in the distribution of soil fauna groups. These results can assist in the classification of some groups of invertebrates as bioindicators of soil quality in agroecosystems.